Unlocking the Path to Success: Exploring the Experiences of Criminology Graduates in Licensure Examination - Bosito, Romel R. (Technium Social Sciences Journal, 2025)
The licensure examination is one of the most crucial moments for graduates, as this examination will test their knowledge and skills. The study aims to explore the experiences of criminology graduates in taking the licensure examination that will serve as the basis for increasing the chances of passing the licensure examination. The study used a descriptive phenomenological design to understand the individual experiences of the participants better. The participants were the eight (8) graduates of the Bachelor of Science in Criminology from the selected universities and colleges in Isabela for the year 2021-2023. The participants are purposely selected based on the following criteria; first, the participants must be a graduate of criminology from the year 2021-2023; second, they must have experience in taking the licensure examination, be able to garner a minimum average of 85 percent, and lastly, participants who refuse to be interviewed were not considered. The study used an unstructured interview guide in gathering the necessary data, interviews, video calls, and google forms were the mode of data collection for this study. The study used thematic analysis to organize the gathered data. The result shows that the challenges faced by the graduates while preparing for the licensure examination are feeling exhausted, financial problems, noisy environment, changeable weather conditions, weak internet connection, lack of individualized guidance, limited and outdated materials, and managing time due to multiple responsibilities. The challenges they faced during the examination were emotional distress, environmental issues, and physical discomfort. The coping mechanisms they utilized while preparing for the licensure examination are time and stress management, social support, resourceful management, and personal well-being. During the examination, graduates cope with the challenges they experience by regulating their emotions and way of thinking, using cognitive and physical refreshments, adaptation, and self-management. To increase the chances of passing the licensure examination, different strategies and support systems are important. These include implementing effective study and review techniques, study attitude and commitment, managing examination questions effectively, and providing institutional support with access to different learning resources and materials. Based on the findings and conclusion of the study, the study recommends that graduates should prepare updated review materials earlier. Educational institutions may also consider purchasing quality review material, offering scholarship grants for the less fortunate graduates, and implement programs to enhance the knowledge of the graduates on the licensure examination. The study also suggests that the Professional Regulation Commission should ensure that examination questions are readable, contain clear images and that the examination area is appropriate for the examinees. Moreover, proctors should be considerate of the personal needs of examinees, especially during lunch breaks and for special necessities.